GAMIFIKASI: PENGARUH GAMIFIKASI BERBASIS PBL UNTUK MENINGKATKAN KEMAMPUAN KEAKTIFAN BELAJAR PESERTA DIDIK - Shofiyah, Ainin; Anwar, Khoirul (JUSEDA, 2024)
One way that teachers can achieve success in learning activities is by choosing a learning model that is appropriate to the learning material, with teachers being able to train students to be more active in the learning process. This research aims to analyze the effect of PBL-based gamification on increasing students' active learning. This research uses a mixed method with a sequential explanatory design to collect data collected using quantitative and qualitative methods. Quantitative data was carried out pre- and post-test by testing data for normality, paired tests, and gain tests, complemented by qualitative data by observation and interviews with students. The subjects of this research were 16 students in class II of SD Negeri 73 Gresik. The analytical results obtained explain that the influence of gamification based on problem-based learning increases students' active learning abilities, with pretest scores ranging from 48 to 65. The average pretest score is 55.56, with a standard deviation of 5,099. This shows that students' pretest scores have quite significant variations. Meanwhile, students' posttest scores ranged from 90 to 100. The average posttest score was 95.38, with a standard deviation of 3,575. shows that the average value of the exam results is at a high level.